1997
DOI: 10.1002/art.1780400113
|View full text |Cite
|
Sign up to set email alerts
|

Fas and Fas ligand expression in the salivary glands of patients with primary Sjögren's syndrome

Abstract: Objective. To assess the role of Fas‐mediated apoptosis in the salivary glands of patients with primary Sjögren's syndrome (SS). Methods. Expression of Fas, Fas ligand (FasL), and bcl‐2 in salivary gland biopsy material was detected in situ by immunohistochemical staining and reverse transcriptase‐polymerase chain reaction. DNA fragmentation in apoptotic cells was assessed by the enzymatic incorporation of labeled nucleotides (digoxigenin‐dUTP). Results. The acinar epithelial cells in SS were Fas+ and FasL+, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
140
1
8

Year Published

1997
1997
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(158 citation statements)
references
References 53 publications
9
140
1
8
Order By: Relevance
“…Fas and FasL have also been recognized in SS (Jonsson et al, 1994;Kong et al, 1997). In the present study, labial minor salivary glands from healthy individuals and SS patients were found to express Fas and FasL.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Fas and FasL have also been recognized in SS (Jonsson et al, 1994;Kong et al, 1997). In the present study, labial minor salivary glands from healthy individuals and SS patients were found to express Fas and FasL.…”
Section: Discussionsupporting
confidence: 65%
“…Fas may also be involved in the pathogenesis of a number of human autoimmune connective tissue disorders, including systemic lupus erythematosus (SLE, Mysler et al, 1994;Emlen et al, 1994), rheumatoid arthritis (Rose et al, 1994) Hashimoto's thyroiditis (Tanimoto et al, 1995;Giordano et al, 1997) and Sjo È gren's syndrome (SS, Ogawa et al, 1996;Kong et al, 1997). SS is an autoimmune disorder characterized by oral and ocular dryness, diminished salivary and lacrimal function, and loss of exocrine parenchymal tissues with replacement by an active mononuclear infiltrate (Fox and Kang, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of apoptosis via the FAS/FAS ligand pathway has been suggested to lead to the salivary gland destruction seen in the autoimmune disorder known as Sjo È gren's syndrome. 1 In addition, apoptosis of normal salivary cells in patients treated with head and neck irradiation or chemotherapeutics can result in reduced salivary gland function, or xerostomia. 2,3 The critical genes in the apoptotic process have been defined genetically in C. elegans, and biochemically in other species.…”
Section: Introductionmentioning
confidence: 99%
“…Implications of the activation of this signalling system may not be limited to the pathogenesis of HT. Recently, acinar epithelial cells from salivary glands in patients with Sjögren's syndrome were shown to express both Fas and FasL mRNA, and the cells died of apoptosis (10). The same signalling system may be activated in other inflammatory conditions in the thyroid leading to hypothyroidism, or even contribute to cell death in autoimmune endocrinopathies such as Addison's disease and insulin-dependent diabetes mellitus.…”
mentioning
confidence: 99%